An Insightful Exploration: Marketing Internship at Charcoal Eats Food Tech Pvt. Ltd. - Karotra, Jatin (ATLAS SkillTech University, 2025)
The internship report titled "An Insightful Exploration: Management Intern at Charcoal Eats" provides a comprehensive overview of my enriching experience as a Marketing Intern at Charcoal Eats, a pioneering Food Tech platform. The report encapsulates the valuable insights and practical knowledge gained during this internship program, which was undertaken during the summer as part of my second-year MBA curriculum at Atlas Skilltech University. Throughout the internship, I actively participated in various aspects of the sales process, including strategizing target identification, prospecting, outreach, Influencer marketing, and GMB management. Under the guidance of Dr. Zuleika Homavazir, my esteemed faculty mentor, I navigated the dynamic world of B2B sales and harnessed the opportunity to bridge the gap between theoretical concept sand real-world applications. The report elaborates on the significance of this hands-on experience, highlighting its impact on my professional growth and aligning my academic knowledge with the demands of the modern business landscape. This executive summary aim stop rovidea glimpse into the detailed findings and reflections shared in the subsequent sections of the report, enabling readers to comprehend the value of this transformative internship experience at Charcoal Eats.
Project Report on An Insightful Exploration: Marketing Internship at Charcoal Eats Food Tech Pvt. Ltd (2023-2025) Under the Guidance of Prof. Zuleika Homavazir
Keywords: Exploration; Management; Marketing; Charcoal Eats; modern business landscape